Development of a Video Media Tutorial on Hair Cutting For Beauty Students at the Private Vocational School Gelora Jaya Nusantara - Dian Maya Sari; Winna Trivera Ginting; Mei Alsih Sihombing; Putri Chairina Zulfiani; Almaida Vebibina (JURNAL ASIMILASI PENDIDIKAN, 2026)
This research is motivated by the low results of students' practical work on the material of haircutting angles, where only 47.06% of students achieved the Minimum Completion Criteria (KKM). Students have difficulty in mastering basic hair cutting techniques, determining partings, and creating appropriate cutting patterns. In addition, the learning media used is still limited to PowerPoint and printed books so that it does not support optimal practical learning. This study aims to develop and determine the feasibility of video tutorial media for haircutting angles for grade XI students of Beauty Treatment at SMK Swasta Gelora Jaya Nusantara. The study used the R&D method with the ADDIE model. The research subjects consisted of 34 students, three material experts, and three media experts. Data collection techniques used a needs questionnaire, expert validation, and product trials. The results showed that the validation of material experts obtained a percentage of 98% and validation of media experts was 95.5% with a very feasible category. The results of student trials showed a percentage of 87% in the small group, 91% in the medium group, and 93% in the large group with a very good category. Thus, the developed video tutorial media is declared very suitable for use in learning hair cutting.